Engineering a synthetic anaerobic respiration for reduction of xylose to xylitol using NADH output of glucose catabolism by Escherichia coli AI21 - Iverson, Andrew (BMC Syst Biol, 2016)
BACKGROUND: Anaerobic rather than aerobic fermentation is preferred for conversion of biomass derived sugars to high value redox-neutral and reduced commodities. This will likely result in a higher yield of substrate to product conversion and decrease production cost since substrate often accounts for a significant portion of the overall cost. To this goal, metabolic pathway engineering has been used to optimize substrate carbon flow to target products. This approach works well for the production of redox neutral products such as lactic acid from redox neutral sugars using the reducing power NADH (nicotinamide adenine dinucleotide, reduced) generated from glycolysis (2 NADH per glucose equivalent). Nevertheless, greater than two NADH per glucose catabolized is needed for the production of reduced products (such as xylitol) from redox neutral sugars by anaerobic fermentation. RESULTS: The Escherichia coli strain AI05 (ΔfrdBC ΔldhA ΔackA Δ(focA-pflB) ΔadhE ΔptsG ΔpdhR::pflBp(6)-(aceEF-lpd)), previously engineered for reduction of xylose to xylitol using reducing power (NADH equivalent) of glucose catabolism, was further engineered by 1) deleting xylAB operon (encoding for xylose isomerase and xylulokinase) to prevent xylose from entering the pentose phosphate pathway; 2) anaerobically expressing the sdhCDAB-sucABCD operon (encoding for succinate dehydrogenase, α-ketoglutarate dehydrogenase and succinyl-CoA synthetase) to enable an anaerobically functional tricarboxcylic acid cycle with a theoretical 10 NAD(P)H equivalent per glucose catabolized. These reducing equivalents can be oxidized by synthetic respiration via xylose reduction, producing xylitol. The resulting strain, AI21 (pAI02), achieved a 96 % xylose to xylitol conversion, with a yield of 6 xylitol per glucose catabolized (molar yield of xylitol per glucose consumed (Y(RPG)) = 6). This represents a 33 % improvement in xylose to xylitol conversion, and a 63 % increase in xylitol yield per glucose catabolized over that achieved by AI05 (pAI02). CONCLUSIONS: Increasing reducing power (NADH equivalent) output per glucose catabolized was achieved by anaerobic expression of both the pdh operon (pyruvate dehydrogenase) and the sdhCDAB-sucABCD operon, resulting in a strain capable of generating 10 NADH equivalent per glucose under anaerobic condition. The new E. coli strain AI21 (pAI02) achieved an actual 96 % conversion of xylose to xylitol (via synthetic respiration), and 6 xylitol (from xylose) per glucose catabolized (Y(RPG) = 6, the highest known value). This strategy can be used to engineer microbial strains for the production of other reduced products from redox neutral sugars using glucose as a source of reducing power.